2003
DOI: 10.1182/blood-2002-12-3899
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of bcr-abl gene expression by small interfering RNA sensitizes for imatinib mesylate (STI571)

Abstract: Bcr-Abl proteins are effective inducers of the leukemic phenotype in chronic myeloid leukemia (CML) and distinct variants of acute lymphoblastic leukemia (ALL). Targeting bcr-abl by treatment with the selective tyrosine kinase inhibitor imatinib has proved to be highly efficient for controlling leukemic growth. However, it is unclear whether imatinib is sufficient to eradicate the disease because of primary or secondary resistance of leukemic cells. Therefore, targeting BcrAbl with an alternative approach is o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
89
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(97 citation statements)
references
References 21 publications
8
89
0
Order By: Relevance
“…This suggests that the number of unique Bcr-Abl interfering motifs are limited and, perhaps, localized. Downregulation of the Bcr-Abl mRNA and protein required multiple transfections, as previously reported [6], and, as suggested, was likely due to siRNA dilution through cell divisions and the long half-life of the Bcr-Abl protein (>48 h). No detectable decrease of the Bcr-Abl protein was found in cells transfected with the rBcr-Abl siRNA preparations.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…This suggests that the number of unique Bcr-Abl interfering motifs are limited and, perhaps, localized. Downregulation of the Bcr-Abl mRNA and protein required multiple transfections, as previously reported [6], and, as suggested, was likely due to siRNA dilution through cell divisions and the long half-life of the Bcr-Abl protein (>48 h). No detectable decrease of the Bcr-Abl protein was found in cells transfected with the rBcr-Abl siRNA preparations.…”
Section: Discussionsupporting
confidence: 77%
“…Two transfections were reported to be required to down-regulate the Bcr-Abl protein in K-562 cells [6]. Western blot analysis showed that synBcr-Abl siRNA lowered the Bcr-Abl protein compared to the irrelevant siRNA control ( Figure 3A).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Several recent studies have demonstrated the ability of small interfering RNAs to reduce Bcr-Abl expression in CD34 þ cells from CML patients (Scherr et al, 2003;Rangatia and Bonnet, 2005) and different established cell lines including the K562 CML cell line (Wohlbold et al, 2003;Rangatia and Bonnet, 2005;Withey et al, 2005), conferring increased sensitivity to apoptosis. So we thought to determine, using inducible shRNA interference, whether Bcr-Abl silencing could mimic the effect of imatinib and PD166326 on K562 cell death and differentiation.…”
Section: Discussionmentioning
confidence: 99%